Divorce law reform, family stability, and children's longterm outcomes - Edvin Hertegård (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
While divorce laws are known to influence family behavior, empirical evidence of their effects on children remains scarce. I shed more light on this by evaluating the Swedish divorce law reform of 1974, which i) liberalized the existing divorce laws and ii) implemented a 6-month parental reconsideration period for divorce. I exploit quasi-experimental policy variation and population-wide register data of 1.17 million Swedish children born 1952-1964 to evaluate the implications of family (in)stability on children's long-term human capital outcomes. The evaluation suggests that exposure to more liberal divorce laws decreases the likelihood of graduating from upper secondary school by 5.6%. Evaluating the reconsideration period, I find that families with greater exposure to this reform element are 18.8%less likely to divorce. The exposed children are also 1.8% more likely to graduate from upper secondary school and have more stable marriage market outcomes as adults. The findings highlight a trade-off between parental freedom of choice related to divorce and externalities on children's outcomes.
Keywords: J12; J13; D13; I24; 330; Divorce law reform; Children's outcomes; Family behavior